The Effect of The Implementation of Single Truck Identification Data (STID) and Occupational Health and Safety on The Smooth Flow of Goods and its Implications on Logistics Efficiency at Tanjung Priok Port - Ribut Risanu; Vika Achmad Danny Angga Putra; Bambang Sumali; Susi Herawati (Dinasti Publisher, 2025)
This study aims to analyze the impact of Single Truck Identification Data (STID) and Occupational Health and Safety (OHS) on the smooth flow of goods and its implications on logistics efficiency at Tanjung Priok Port. The main issue faced at the port is the irregularity in the distribution of goods due to delays in vehicle verification and suboptimal safety conditions, which reduces logistics efficiency and affects the operational performance of the port. This study adopts a quantitative approach with a cross-sectional design, involving 380 respondents, including truck drivers, terminal operators, and port management, selected through purposive sampling. Data collection was carried out via questionnaires and analyzed using SmartPLS to test the direct and indirect effects among the variables. The results indicate that STID significantly affects the smooth flow of goods (t-statistic = 3.483) and logistics efficiency (t-statistic = 2.730), while OHS significantly affects the smooth flow of goods (t-statistic = 4.192) and logistics efficiency (t-statistic = 5.125). Additionally, both variables also have an indirect impact on logistics efficiency through the smooth flow of goods. In conclusion, the implementation of STID and OHS can improve logistics efficiency. It is recommended to strengthen the implementation of STID and the OHS program at the port. Future research could explore this further using a qualitative approach and longitudinal analysis.